2009
DOI: 10.1007/s00534-009-0069-7
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection versus radiofrequency ablation for small hepatocellular carcinomas within the Milan criteria

Abstract: In patients with small HCCs within the Milan criteria, hepatic resection should still be employed for those patients with a single tumor and well-preserved liver function. RFA should be chosen for patients with an unresectable single tumor or those with multinodular tumors, regardless of the grade of liver damage. In order to increase long-term oncological control, surgical RFA seems preferable to percutaneous RFA, if the patient's condition allows them to tolerate surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 31 publications
(47 reference statements)
6
77
1
Order By: Relevance
“…Due to the shortage of organ donor and the risk of disease progress on the waiting list, resection was suggested as the first-line treatment to the patients with small HCC and preserved liver function, and could achieve the favorable 5-year OS rate. The 5-year OS rate of resected HCC meeting Milan Criteria, according to the recent reports, ranged from 27% to 80% (Baccarani et al, 2008;Ueno et al, 2009;Lim et al, 2012), even 10-year OS rate in some centers could reach to 56% , and the 5-year RFS rate ranged from 21% to 57% (Ochiai et al, 2004;Lee et al, 2010;Lim et al, 2012). In our study, we observed that the 1-, 3-and 5-year OS rate were 96%, 81% and 76% respectively, and the 1-, 3-and 5-year RFS rate were 68%, 51% and 39% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the shortage of organ donor and the risk of disease progress on the waiting list, resection was suggested as the first-line treatment to the patients with small HCC and preserved liver function, and could achieve the favorable 5-year OS rate. The 5-year OS rate of resected HCC meeting Milan Criteria, according to the recent reports, ranged from 27% to 80% (Baccarani et al, 2008;Ueno et al, 2009;Lim et al, 2012), even 10-year OS rate in some centers could reach to 56% , and the 5-year RFS rate ranged from 21% to 57% (Ochiai et al, 2004;Lee et al, 2010;Lim et al, 2012). In our study, we observed that the 1-, 3-and 5-year OS rate were 96%, 81% and 76% respectively, and the 1-, 3-and 5-year RFS rate were 68%, 51% and 39% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…RFA and MWA techniques utilise high frequency radio-waves and micro-waves, respectively, to kill tumour tissues by heat. Although several studies have reported better diseasefree survival and a lower frequency of recurrence after surgical resection compared to RFA [10,11] , others report better overall survival and disease-free survival for HCC patients with multi-nodular tumours following RFA [12] . Recently, Simo et al [13] reported no difference regarding the efficacies of MWA and RFA procedures.…”
Section: Hepatocellular Carcinoma and The Unmet Medical Needsmentioning
confidence: 99%
“…The outcome of partial hepatectomy in cirrhotic patients has improved remarkably in recent years with improved surgical techniques and perioperative care (7,8): mortality is reported to range between 0% and 5% in tertiary centers and postoperative hepatic decompensation to be about 4% (8,(20)(21)(22) (20,(24)(25)(26). Regarding transplantability of HCC recurrence, the literature reports that tumor recurrence suitable for salvage transplantation occurs with a median of 60%, ranging from 23% to 89% (20,22,(27)(28)(29)(30).…”
Section: Variables Considered After Hrmentioning
confidence: 99%